Genome‐wide prediction of synthetic rescue mediators of resistance to targeted and immunotherapy - Avinash Das Sahu; Joo S Lee; Zhiyong Wang; Gao Zhang; Ramiro Iglesias‐Bartolome; Tian Tian; Zhi Wei; Benchun Miao; Nishanth Ulhas Nair; Olga Ponomarova; Adam A Friedman; Arnaud Amzallag; et al. (Molecular Systems Biology)
Abstract Most patients with advanced cancer eventually acquire resistance to targeted therapies, spurring extensive efforts to identify molecular events mediating therapy resistance. Many of these events involve synthetic rescue (SR) interactions, where the reduction in cancer cell viability caused by targeted gene inactivation is rescued by an adaptive alteration of another gene (the rescuer). Here, we perform a genome‐wide in silico prediction of SR rescuer genes by analyzing tumor transcriptomics and survival data of 10,000 TCGA cancer patients. Predicted SR interactions are validated in new experimental screens. We show that SR interactions can successfully predict cancer patients’ response and emerging resistance. Inhibiting predicted rescuer genes sensitizes resistant cancer cells to therapies synergistically, providing initial leads for developing combinatorial approaches to overcome resistance proactively. Finally, we show that the SR analysis of melanoma patients successfully identifies known mediators of resistance to immunotherapy and predicts novel rescuers.